(untitled) (Proceedings of International Conference on Special Education, 2015)
Child development professionals, psychologists, learning scientists and other childhood experts agree that play is an essential component of healthy childhood development (Ginsburg and Committee on Psychosocial Aspects of Child and Family Health, 2007). This ethnographic research was set forth to examine and explore the practices and experiences of young learners and their educators who were participating in playful/play-based science program and how this approach influenced the collective dynamics the school that follows the principles of age-appropriate inclusive education program. Particularly, this study sought to investigate these particular research questions: 1) How do children engage in playful science?; 2) What skills were children developing in their playful science activities?; 3) What are the perceptions of teachers and parents regarding playful science?; and 4) What are the innovative teaching approaches do teachers’ used in playful science activities? The partakers of the study included preschool learners, school administrator, special and general (preschool) education teachers, parents and caregivers. Data were analyzed and triangulated within multiple sources to ensure substantiation thus identifying discrepancies and commonalities specifically using in-depth semi-structured interviews and focus group discussions with administrators, teachers, parents and caregivers, playful science activities observations, document and archival exploration, portfolios and videotape analyses. Data analysis was done concurrently with data collection through an interactive, recursive and dynamic process and quotations were used for exposition and clarification of major themes. The findings of this study revealed accounts of significant harmony between families and the school at both theoretical and application levels to achieve realization of playful science. Children’s interactions in playful science, with materials, peers, and adults, provided an opportunity for children’s holistic development and adults assumed roles as scaffold, facilitator and mediator while children were actively involved with a variety of strategies.